Salivary and Gingival Crevicular Fluid Levels of Interleukin-1β, Interleukin-17, Interleukin-36β, Interleukin-37 and Interleukin-38 In Healthy and Periodontitis Patients: A Cross-sectional Study - Alreshaid, Reem. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Periodontology.; Advisor: Evangelos Papathanasiou.; Committee: Mabi Singh, Livia Valverde, and Matthew Finkelman.; Keyword: Dentistry.